A new species and new records of Cryptodacus (Diptera: Tephritidae) from Colombia, Bolivia and Peru - Rodriguez, Pedro Alexander; Rodriguez, Erick J.; Norrbom, Allen L.; Arévalo, Emilio (Zootaxa, 2016)
Cryptodacus bernardoi Rodriguez & Rodriguez, new species, is described from Colombia. It was reared from fruits of Phoradendron sp. near piperoides (Kunth) Trel. New distribution records are reported for Cryptodacus ornatus Norrbom from Colombia and Peru, for Cryptodacus trinotatus Norrbom & Korytkowski from Colombia, and for Cryptodacus obliquus Hendel from Bolivia and Peru. The female abdomen and terminalia of C. obliquus is described for the first time. The Norrbom & Korytkowski (2008)`s key to species was modified to include C. bernardoi n. sp.